Pemberdayaan Masyarakat Melalui Pembuatan Dan Pembagian Masker Dalam Mengatasi Penyebaran Dan Penularan Covid-19 - Inayah, Nurul; Ekaningsih, Lely Ana Ferawati; Susanti, Nawal Ika (IAI Darussalam, 2021)
The best way to prevent Covid-19 is to avoid factors that can cause infection with this virus. The role of the government in taking policies to break the chain of transmission of Covid 19 to the surrounding community as has been carried out by the Jajag Village Government, Gambiran District, Banyuwangi Regency during the pandemic by 1) spraying in every community house by means of each community member a minimum of Rp. 15,000 for labor costs and the purchase of disinfectant. Spraying is also carried out on major roads and crowds; 2) When carrying out community activities or village employees, they are required to wear masks, keep a distance and wash their hands with soap before entering the room; 3) The Jajag Village apparatus also distributed free masks to the local community as the only prevention from the corona virus; 4) Provide information about health by traveling around the village in a village car, information on the dangers of the Covid-19 pandemic, minimizing residents to leave their homes and urging the public to pay attention to policies made by the government; and 5) Calling on the community to make hand washing stations filled with air and antiseptic which are placed in front of every house as well as in village mosques. The need to empower the community in making masks from household materials that can be used is a solution to reduce the cost of buying masks